2021
DOI: 10.1186/s13045-021-01179-y
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs link metabolic reprogramming to immune microenvironment in cancers

Abstract: Altered metabolic patterns in tumor cells not only meet their own growth requirements but also shape an immunosuppressive microenvironment through multiple mechanisms. Noncoding RNAs constitute approximately 60% of the transcriptional output of human cells and have been shown to regulate numerous cellular processes under developmental and pathological conditions. Given their extensive action mechanisms based on motif recognition patterns, noncoding RNAs may serve as hinges bridging metabolic activity and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 321 publications
(295 reference statements)
0
27
0
Order By: Relevance
“…More and more evidence confirmed that noncoding RNA (ncRNA) plays an important role in mediating breast cancer genesis and progression [ 6 ]. MicroRNAs (miRNA) are small noncoding RNAs with nucleotides of 19-25 in length that can regulate posttranscription gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidence confirmed that noncoding RNA (ncRNA) plays an important role in mediating breast cancer genesis and progression [ 6 ]. MicroRNAs (miRNA) are small noncoding RNAs with nucleotides of 19-25 in length that can regulate posttranscription gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept and these research results, TVEC has been approved by the US FDA for clinical use in patients with advanced malignant melanoma. While intratumoral administration of immunostimulatory agents and noncoding RNAs in solid tumors is a plausible method [ 140 ] and may remodel tumor metabolism and the immune microenvironment [ 141 , 142 ], due to the pathogenesis of AML and MDS, intratumoral vaccination to locally activate tumor-infiltrating DCs may not be widely applicable except in the cases with chloroma as the only presentation.…”
Section: Methods For Vaccine Deliverymentioning
confidence: 99%
“…Cancer cells and TAMs establish a mutual metabolic communication, with cancer cells promoting the M2-like phenotype through the secretion of lactate, and TAMs increasing glucose availability for tumor cells [84]. Non-coding RNAs are crucial mediators of this interplay [85,86].…”
Section: Non-coding Rnas In the Regulation Of Bc Cells And Tam Metabo...mentioning
confidence: 99%